Retirement planning - As assessment of current attitudes and views. - Seetoh, Yin Ling. (2008)
Singaporeans are enjoying a better quality of life than the previous generation. To maintain their lifestyles in their retirement years. Singaporeans are encouraged to start retirement planning early. In view of the current trends - demographic, social and economic, financial planning is needed to overcome financial hurdles in the retirement years.